LESSON STUDY SEBAGAI LEARNING COMMUNITY UNTUK MENINGKATKAN KOMPETENSI PROFESIONALITAS PESERTA PROGRAM PENDIDIKAN PROFESI GURU KIMIA FKIP UNIVERSITAS RIAU - Maria Erna; Diana Tejawati; Ade Achmadi; Leo F Manalu; Martina Eka Desvita (Jurnal Pendidikan Kimia Universitas Riau, 2016)
Research on the ability of participants Professional Teacher Education Program (TEP) Chemistry FKIP University of Riau in implementing have been done Lesson Study (LS) as the Learning Community (LC) with the aim of improving professional competence as chemistry teacher candidates. The number of participants total 3 TEP guided implement the LSLC in Chemistry Laboratory FKIP and application implemented in SMAN 12 Pekanbaru. Learning implementation plan compiled by participants of TEP Chemistry Education has improved the category of B (Good) on the plan I and II to A (Very Good) on plan III. Value competence participants TEP Chemistry Education in the implementation of learning also showed an improvement of category K (Less) on the open lesson I and II into a C (Enough) in the open lesson III. The results of this study prove that the application LSLC at SMAN 12 Pekanbaru can develop professional competence of participants TEP Chemistry Education FKIP University of Riau in a sustainable and secure the rights of all students to get a high quality education.